Radio Map Framework for GSM Positioning - Brida, Peter; Benikovsky, Jozef (Communications - Scientific letters of the University of Zilina, 2009)
This paper introduces radio map framework for creation of GSM (Global System for Mobile communications) network radio maps. These radio maps are structured in the way that they can be utilized later on as a data source for fingerprinting-based localization methods. Attributes of fingerprinting localization method as well as particular radio signal parameters are explained. The framework handles data measurement, data transfer and data visualization scenarios. Data are basically various radio signal parameters coupled with position coordinates. These data make up a database, which allows centralized storage and opens a path to service-oriented localization architecture in the future. Visualization provides means to verify radio map quality, distribution and density in perceptible and user friendly way as well as means to present and publish achieved results. Entire system is aimed to provide usability by multiple users and further optimization. Centralization allows easy implementation of changes and system maintenance at one place.